Design and validation of a questionnaire (LLQ) on facilitating the development of learning to learn competence in university educators - Iñurrategi, Nagore; Martínez, Agurtzane; Muela, Alexander (Anales de Psicología / Annals of Psychology, 2021)
Within the European Higher Education Area framework, educators must have acquired professional skills in order to promote different competences in the learning to learn competence, which refers to the self-regulation capacity of the learning process itself. The objective of this work was to design and validate a questionnaire to measure the learning facilitator contexts activated by university educators for the development of the learning to learn competence, LLQ. First of all and based on a theoretical and empirical review, 86 items belonging to 7 dimensions were defined. Next, content validity (n = 20 experts), validity based on the response processes (n = 10 teachers), validity based on the internal structure (n = 415 teachers), concurrent validity and external validity were examined. Results showed adequate psychometric quality, internal consistency, reliability and goodness of fit. The final version of the LLQ comprised 4 dimensions and 39 items. This instrument can be considered to be a quick applicable, valid and reliable tool in order to identify the development of the learning facilitator contexts in the growth of the learning to learn competence at university. Likewise, it can also serve to detect training needs in the development of such competence in university educators.